Techniques of isolation, identification and occurrence of halotolerant Fusarium species in terrestrial saline soils - Ammar, Rofaida; Takhi, Djalila (Laghouat : Université Amar Telidji - Département de biologie, 2022)
Fusarium is a well-known filamentous fungus that can be found in a variety of environments,including soil. This genus is among the most common mycobiota in hypersaline soils. Identifying fungus as Fusarium has generally relied on morphological identification methods. Scientists adopted the morphological technique to address fungal diversity studies issues when more accurate and effective molecular identification technologies became available. The main objective of this work is to present a summary of Isolation, identification and occurrence of halotolerant Fusarium species in terrestrial saline soils as well as the effect of the extreme conditions of these habitats on their variability. 13 isolated fusarium species from diverse geographic regions in saline soils were identified as fusarium species from the studies analyzed. however, Different physicochemical factors are present in these regions. The occurrence of several Fusarium species varies considerably from one location to another. The diversity in species is most likely linked to the physicochemical properties of each analyzed habitat, such as temperature, pH, salinity…etc. most of isolates could tolerant up to 12.5% of NaCl (g/l). Only Acuminatum could tolerant 10% of NaCl, wish optimum of 2.5%. Fusarium was the most dominant genera, while F. equseti is the most abundant species (37.7%). As a comparison element, four investigations on non-saline soils were considered. Six species are found in these soils that are comparable to those found in saline soils. The isolated species most likely survived and adapted to their extreme environment.